Perencanaan Eko-Drainase Ramah Lingkungan sebagai Wujud Pengabdian Masyarakat di Dusun Sendang Biru Selatan - Trianus, Mimin; Utami, Sri; Fitriani; Uzia, Wa Ode Ulfa (Anoa : Jurnal Pengabdian Masyarakat Fakultas Teknik, 2024)
Eco-drainage is an environmentally friendly infrastructure solution designed to mitigate flood risks. Flooding issues often arise due to damage or mismatched dimensions of drainage systems in residential areas. This study aims to plan and develop a new drainage system concept in the Very Simple Housing Area, South Sendang Biru Hamlet. The methodology includes a planning approach based on detention system, retention system, and infiltration system concepts. Collected data were analyzed to produce optimal planning concept recommendations. The results of this study are expected to serve as guidelines for the local community and government to improve drainage systems for sustainable flood prevention.